Studi Rasionalitas Penggunaan Antibiotika di RSUD DR. Murjani Sampit - darini kurniawati (LPPM Universitas Sari Mulia, 2021)
Background Antibiotics are the most widely used type of drug due to the high incidence of infection in Indonesia. From the results of the preliminary study for 3 days prospectively, as many as 44 patients who received treatment, 37 patients (87%) received antibiotic therapy. There is the use of expensive antibiotics from the 3rd generation cephalosporin group, there are 4 trade names, 2 generation cephalosporins and 1 there are 6 trade names. Expensive sulbenicin and aminoglycoside derivatives are also found, Gentamicin and Kanamycin. The relatively cheap antibiotics are chloramphenicol, tetracycline, cotrimoxazole, but various brands of these products are popular with